Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual terhadap Engagement Pegawai Hotel Mandalawangi di Kota Tasikmalaya - Anisa Anzani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the influence of emotional intelligence and spiritual intelegence towards non manager employee engagement in Mandalawangi Hotel. The type of this study is quantitive method. The population on this study is 35 non manager employee of Mandalawangi Hotel. Sampling technique on this study is saturated sampling 35 non manager employee of Mandalawangi Hotel. Data analysis on this study is multiple regression analysis using SPSS ver. 25 software. The result of this study shows that emotional intelligence and spiritual intelegence simultaneously have influence towards non manager employee engagement in Mandalawangi Hotel. emotional intelligence partially has influence towards non manager employee engagement in Mandalawangi Hotel. Spiritual intelegence partially has no influence towards non manager employee engagement in Mandalawangi Hotel